HUBUNGAN VOLUME PROSTAT DENGAN SKOR IPSS PADA PENDERITA BENIGN PROSTATIC HYPERPLASIA (BPH) DI RSU HAJI MEDAN - MAGHFIRA, JIHAN; FATHURRAHMAN, HASRONI; RIZALDI, ARIL (JURNAL ILMIAH SIMANTEK, 2023)
Benign prostatic hyperplasia (BPH) is a benign neoplasm in which the periurethral state of the prostate experiences hyperplasia. Benign prostatic hyperplasia (BPH) can cause complaints that interfere with daily activities, although it is rarely life-threatening. These complaints can be in the form of lower urinary tract symptoms (LUTS). The IPSS questionnaire is used as a measure of the severity of lower urinary tract symptoms (LUTS). Prostate volume is important as a reference for the severity of the progression of benign prostatic hyperplasia (BPH) or the outcome of this disease in the form of acute urinary retention (AUR), as well as the response to treatment. This study aims to determine the relationship between prostate volume and IPSS score in patients with Benign prostatic hyperplasia (BPH) at RSU Haji Medan. This study used a retrospective analytic observational study design with a cross-sectional design approach that met the inclusion and exclusion criteria and was carried out in the urology department of RSU Haji Medan. Based on the results of a study conducted from September to December at the Haji Medan General Hospital, 93 samples were obtained. The highest incidence of BPH was in the age range of 61–70 years, with 40 people (43.0%). The highest volume was in classification 1 (20-39cc), with as many as 53 people (57.0%), and the most frequent degree was the degree of severity, with as many as 39 people (41.9%). The results of the Spearman correlation test showed that there was a significant relationship between volume and the IPSS score in patients with benign prostatic hyperplasia (BPH), p<0,001 with a correlation coefficient (r = 0.853), indicating a very strong correlation, where the value of the correlation coefficient is positive, which means that the relationship between the two variables is unidirectional. Prostate volume and IPSS score have a significant relationship in patients with benign prostatic hyperplasia (BPH).